Normal Face Detection Over a Range of Luminance Contrasts in Adolescents With Autism Spectrum Disorder - Norton, Daniel J.; McBain, Ryan K.; Murray, Grace E.; Khang, Juna; Zong, Ziqing; Bollacke, Hannah R.; Maher, Stephen; Levy, Deborah L.; Ongur, Dost; Chen, Yue (Frontiers in Psychology, 2021)
Face recognition is impaired in autism spectrum disorders (ASD), but the reason for this remains unclear. One possibility is that impairments in the ability to visually detect faces might be a factor. As a preliminary study in this vein, we measured face detection ability as a function of visual contrast level in 13 individuals with ASD, aged 13-18, and 18 neurotypical controls (NC) in the same age range. We also measured contrast sensitivity, using sinusoidal grating stimuli, as a control task. Individuals with ASD did not differ from controls in face detection (p>.9) or contrast detection (p>.2) ability. Performance on contrast and face detection was significantly correlated in ASD but not in NC. Results suggest that the ability to visually detect faces is not altered in ASD overall, but that alterations in basic visual processing may affect face detection ability in some individuals with ASD.